New species and records of earthworms (Annelida, Oligochaeta) in plantain cropping systems in Colombia's coffee-growing region - M., Alexander Feijoo; Z., Luis Fernando Zuluaga; R., Ligia Janneth Molina (Zootaxa, 2018)
Two new earthworm species, one of Glossodrilus Cognetti, 1905 and the other of Martiodrilus (Maipure) Righi, 1995, are described from material collected from the coffee-growing region located in central-western Colombia: Glossodrilus chaguala sp. nov., and Martiodrilus (Maipure) quimbayaensis sp. nov. New records for this region are also reported for Glossodrilus griseus, Glossodrilus lacteus, Glossodrilus panikita, Aptodrilus fuhrmanni, Periscolex columbianus, Periscolex coreguaje, Pontoscolex (Pontoscolex) corethrurus, Dichogaster (Diplothecodrilus) affinis, Dichogaster (Diplothecodrilus) bolaui, Dichogaster (Diplothecodrilus) saliens, Amynthas (Amynthas) gracilis, Amynthas minimus, and Perionyx excavatus.